2012
DOI: 10.1371/journal.pone.0043614
|View full text |Cite
|
Sign up to set email alerts
|

Light Use Efficiency over Two Temperate Steppes in Inner Mongolia, China

Abstract: Vegetation light use efficiency (LUE) is a key parameter of Production Efficiency Models (PEMs) for simulating gross primary production (GPP) of vegetation, from regional to global scales. Previous studies suggest that grasslands have the largest inter-site variation of LUE and controlling factors of grassland LUE differ from those of other biomes, since grasslands are usually water-limited ecosystems. Combining eddy covariance flux data with the fraction of photosynthetically active radiation absorbed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…For the alpine meadow HaM site, the annual maximum LAI was 3.1 in August, 2001 and 3.8 in July, 2002 (Kato et al, 2004). More detailed ecological and climate information can be found in Chen et al (2009a,b) for sites of Xi1, Xi2, Du2, and Ku2, in Wang et al (2008) and Wang and Zhou (2012) for site Xfs, and in Kato et al (2004Kato et al ( , 2006 for site HaM.…”
Section: Study Area and Flux Tower Datamentioning
confidence: 97%
“…For the alpine meadow HaM site, the annual maximum LAI was 3.1 in August, 2001 and 3.8 in July, 2002 (Kato et al, 2004). More detailed ecological and climate information can be found in Chen et al (2009a,b) for sites of Xi1, Xi2, Du2, and Ku2, in Wang et al (2008) and Wang and Zhou (2012) for site Xfs, and in Kato et al (2004Kato et al ( , 2006 for site HaM.…”
Section: Study Area and Flux Tower Datamentioning
confidence: 97%
“…Using RS time series and meteorological data, apple fruit yields were also predicted by the CASA SR model. A previous study demonstrated that the parameters of the CASA model were often affected by several factors, such as the vegetation type, geographical location, and environmental conditions [13,35,36,56,57]. Therefore, this study optimized the parameters of the CASA model to improve its apple fruit yield prediction accuracy.…”
Section: The Casa Model For Apple Yield Predictionmentioning
confidence: 98%
“…The maximum light use efficiency of the original CASA model was assigned a value of 0.389 g C/MJ [35]. However, many studies have demonstrated that the maximum light use efficiency displays large differences among vegetation types and environmental conditions [56,57,60]. Zhu et al [58] proposed that the maximum light use efficiency values ranged from 0.159 to 2.553 g C/MJ for woody vegetation in China.…”
Section: The Casa Model For Apple Yield Predictionmentioning
confidence: 99%
“…LUE demonstrated significant year-to-year variation in a peatland pasture in Canada during 2014-2015 [16]. LUE increased and decreased in the opposite direction on two different grassland types in Inner Mongolia, China [17]. Temperature, precipitation, radiation, soil moisture, and nutrients are key factors limiting the photosynthetic processes of grassland ecosystems in different regions [14,15,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%